Acetic acid induced synthesis of laminated activated carbon nitride nanostructures. (October 2016) - Fan, Hai; Wang, Nan; Tian, Yijun; Ai, Shiyun; Zhan, Jinhua
Abstract: Graphitic carbon nitride (g-C3 N4 ), composed of only non-metallic elements, possesses a graphene-like structure and an appropriate band gap around 2.7 eV. It is finding its promising applications in sustainable chemistry. In this paper, highly ordered laminated porous carbon nitride nanostructures (OLP-C3 N4 ) are successfully prepared via a novel two-step hydrothermal-calcination method using acetic acid as the order-inducing agent and pore-forming agent. Acetic acid and melamine are first hydrothermally synthesized to form a solid precursor. Then, the precursor is calcinated to obtain the product. The electrostatic interaction existed between acetic acid and melamine in water during the hydrothermal process is considered to play a key role on the formation of layered nanostructures. While, carboxyl group in acetic acid is favorable for the porous structure of the products. The prepared carbon nitride nanostructures exhibit high surface area and show excellent electric transport and optical properties, which may have wide applications in catalytic, adsorptive and battery materials fields. This work opens a novel way for the preparing hierarchical porous materials with unique properties.